Fermented beverage benefits: a comprehensive review and comparison of kombucha and kefir microbiome - Ann, Qi Chong; Siew, Wen Lau; Nyuk, Ling Chin; Talib, Rosnita A.; Kadir Basha, Roseliza (Multidisciplinary Digital Publishing Institute, 2023)
Beverage fermentation is an ancient ritual that has been practised for millennia. It was slowly disappearing from households and communities due to the advancement of manufacturing technology and the marketing of soft drinks until the recent revival of the beverage fermentation culture due to an increase in the demand for health drinks amid the COVID-19 pandemic. Kombucha and kefir are two well-known fermented beverages that are renowned for their myriad of health benefits. The starter materials for making these beverages contain micro-organisms that act like microscopic factories producing beneficial nutrients that have antimicrobial and anticancer effects. The materials modulate the gut microbiota and promote positive effects on the gastrointestinal tract. Due to wide variations in the substrates and types of micro-organisms involved in the production of both kombucha and kefir, this paper compiles a compendium of the micro-organisms present and highlights their nutritional roles.